A aprendizagem da geometria espacial potencializada por meio de um aplicativo de realidade aumentada na perspectiva do mobile learning - Resende, Bruno (2019)
This dissertation addresses an investigation into the learning of spatial geometry through mobile devices using an Augmented Reality application. The objectives were to analyze, verify and understand how mobile learning presents itself in the process of studying solids of revolution and polyhedra in the interaction with smartphones. The present work had the theoretical as-sumptions of authors who write conceptions about learning with technology, learning of geo-metry, Mixed Reality, Augmented Reality, m-learning and markers inserted in Education. Technology learning highlights arguments about the most dynamic ways technology brings to the educational environment. Geometry is evidenced as one of the contents that present more difficulties for students of High School, but at the same time benefited by the advances of com-puterized technologies. The Mixed Reality is conceived as a resource that contributes to the interaction with digital information in a real environment and the Augmented Reality, conside-red as a Mixed Reality, promotes a new experience with three-dimensional objects in the lear-ning of spatial geometry. The m-learning is described, through the ideas of the authors that deal with the subject, as a modality of mobile learning that allows the students to be the authors of the own knowledge. Another theoretical conception inserted in the research is the use of Aug-mented Reality markers as an alternative to potentialize the learning process. The research has a qualitative character based on the Discursive Textual Analysis method. During the research, the instruments of data collection used were direct observations, field diaries and questionnai-res. The investigation occurred in a private school in the city of Porto Alegre through an activity with the use of an Augmented Reality application. For data analysis, text mining techniques with a web application using the python programming language were used in order to organize and systematize the descriptive data to facilitate the procedures that make up the Discursive Textual Analysis. Given the results and from the emerging categories of research, it can be affirmed that mobile learning presents itself as an interactive contribution to learning and as an aid in the construction of mathematical knowledge. As final considerations, the research highlights that the learning of spatial geometry with an Augmented Reality application promo-ted the students' engagement, enriched the development of new forms of learning and contribted to a more autonomous study evidencing the student as the central object of learning